The Religious Work of Beverly Jenkins’s Black Historical Romance - Jeania Ree V. Moore (Journal of Popular Romance Studies)
This article argues that Beverly Jenkins’s Black historical romance is religious. In offering this analysis, this article draws attention to a long-standing African American religious historiographic tradition known as chronicling. From Maria Stewart to Frances Ellen Watkins Harper and beyond, Black chroniclers have written Black history with the sacred aim of rehabilitating Black historical consciousness: rewriting the past to empower the present and reimagine the future. Jenkins innovates in and amplifies the religiosity of Black chronicling through the erotic, a powerful religious resource embraced by Black women theologians, ethicists, and writers. This article draws on Black womanist and Black feminist scholarship to show how Jenkins centers desire, interiority, and pleasure within Black women’s moral agency and affirms Black women’s embodied flourishing. Bringing together African American historiography and popular romance studies with Black women’s theological ethics and literature, this article examines Jenkins’s novels, her formation as a writer, and her reader reception to shine a new light on the many facets of Black popular romance. Jenkins’s Black historical romance radically continues the religious legacy of chronicling Black history, effecting personal and communal transformation, liberation, and repair with the truth “‘of who [Black people] are and…were’” (Jenkins in Amos et al.).